Improving quality and treatment of water and vegetables in fresh-cut vegetable processing : Doctoral Dissertation - Lehto, Marja (Natural Resources Institute Finland (Luke), 2019)
Fresh-cut vegetables have been cleaned, peeled, chopped, sliced, or diced and then packaged but not heated. The fresh-cut vegetable processing industry uses large volumes of water. This water is utilized by hygiene and cleaning processes and for cooling of the products. Knowledge has been lacking about waters created and the water use in different stages of the fresh-cut vegetable processing. Obtaining information about the water use and waste water production is important for recocnizing critical phases for risk management and for evaluating the need of water treatments. The aim of this study was to improve the processing of fresh-cut vegetables through collecting information on the hygienic level of waters and vegetables, decontamination methods and their efficacy, water use and waste waters which helps companies to improve their processes and self-monitoring activities. One aim of this study was to also evaluate on-farm waste water treatment systems carrying out peeling of vegetables. Water consumption, measured in six fresh-cut processing companies in this study, was 2.0–6.5 m3/t per finished product. The water consumption varied in the same company between months and according to season, volumes of vegetables processed, and the quality of raw material. Through regular measurement of water consumption, it is possible to decrease water use in fresh-cut vegetable processing. In the present study, water consumption decreased by 15% over the course of the three-year period examined. This may decrease costs and improve sustainability of the production. Vegetables contain 90‒96% water; the remainder is composed of components such as carbohydrates, proteins and nutrients. In vegetal cells, water is present in different forms; part of this water can easily be removed and a part cannot. Depending on their size, the substances of which vegetables are composed form different kinds of solutions in combination with water. Most of the organic load and nutrients of the vegetables processed were released into water from the peeling of root vegetables, whereas the volume of the water came primarily from the rinsing and washing of vegetables. Wash-ing is an important step in fresh-cut vegetable processing; it removes soil and debris, and reduces microbial populations residing on the vegetable surface. Washing is often the only step that can remove foreign material and tissue exudates, as well as inactivate pathogens. Water plays a dual role in the fresh-cut vegetable processing: it both reduces and transmits microorganisms to vegetables. The high quality of water used in processing is important, and can be attained through water decontamination or by using new potable water that is changed continuously during the process. The high operation-al cost of water use has resulted in the industry-wide common practice of the reuse or recirculation of process water. Fresh-cut vegetables may be contaminated by pathogens in different stages and different ways after harvest. Pathogenic microorganisms can cause severe outbreaks of foodborne disease. The microbiological quality of vegetables changes during processing. The total microbial counts in peeled and cut carrots were lower than in whole washed carrots, but higher in grated than in cut carrots. The total microbial count was lower in process water than in wash water of carrots. Pathogenic Yersinia enterocolitica was detected in many carrot and water samples by sensitive RT-PCR, but not by the cultivation method. The data concerning treatment of process water of fresh-cut wagetable processing is quite scarce, in particular concerning the effect of treatments on yersinia. Water de-contamination methods neutral electrolyzed water (NEW), chlorine dioxide (ClO2), or-ganic acids and UV-C was evaluated, specially on yersinia, E. coli and Candida lambica (yeast) in this study. The effect of decontamination on different microbes in water dif-fers with, e.g., time, concentration, decontamination method, and turbidity of water. Technically- and economically effective chlorine-alternative decontamination technologies are the goal of the fresh-cut industry. In Finland, and in many other EU countries as well, chemical treatments of vegetable process waters are restricted in food legislation, but allowed in other countries. Published information concerning the functioning and feasibility of small on-farm waste water treatment plants are few. Waste water generated from vegetable production contains high concentrations of biochemical oxygen demand (BOD) and suspended solids (SS). One aim of this study was to evaluate on-farm waste water treatment systems carrying out peeling of vegetables. Primary treatments of waste water remove coarse solids, reduce organic matter content and adjust pH. Secondary, biological, wastewater treatment removes soluble organic matter and nutrients from water. Bio-logical waste water treatment, such as a sequencing batch reactor or a trickling filter, are used for treating of vegetable processing waste water in small scale companies in rural areas. In the case of both systems, the requirements set in legislation were met. Tertiary treatment can be used if waste water is reused in subsequent vegetable processing or recycled for irrigation of food crops. Fresh-cut vegetable processing companies produce high-quality fresh-cut produce with appropriate inputs and processes. Each company must establish its own specific validation protocols for evaluating their processes. The aim is to minimize the risks and produce healthy, safe, fresh and easy-to-use vegetables for consumers.
Keywords: decontamination; carrot; fresh-cut vegetable; lettuce; microbiological quality; processing; process water; wash water; waste water treatment; water use